2011
DOI: 10.1007/s00421-011-2124-8
|View full text |Cite
|
Sign up to set email alerts
|

Ankle proprioception is not targeted by exercises on an unstable surface

Abstract: Laboratory study using a repeated measures design. The aim of this study was to determine if ankle proprioception is targeted in exercises on unstable surfaces. Lateral ankle sprain (LAS) has recurrence rates over 70%, which are believed to be due to a reduced accuracy of proprioceptive signals from the ankle. Proprioceptive exercises in rehabilitation of LAS mostly consist of balancing activities on an unstable surface. The methods include 100 healthy adults stood barefoot on a solid surface and a foam pad ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 37 publications
(47 reference statements)
5
52
1
Order By: Relevance
“…(1) The mean COP speed ('COP speed'), which is the total COP path length divided by trial time [2,[28][29][30]. (2) The mean absolute COP sway ('COP sway'), which is the mean absolute distance of the COP trajectory to the average COP position [3,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) The mean COP speed ('COP speed'), which is the total COP path length divided by trial time [2,[28][29][30]. (2) The mean absolute COP sway ('COP sway'), which is the mean absolute distance of the COP trajectory to the average COP position [3,31].…”
Section: Discussionmentioning
confidence: 99%
“…Single leg balance performance has been significantly related to functional performance [1][2][3] and injuries, such as ankle sprains [4] and anterior cruciate ligament (ACL) deficiency [5]. However, it has been suggested that single leg jump landing tasks may better detect differences in sensorimotor function than static single leg stance, since they are more challenging and sport specific [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…13,26 The STSTS task on an unstable support surface is ultimately challenging the sensorimotor system (including the proprioceptive system) because this condition requires additional reweighting of the proprioceptive signals due to the decreased reliability of proprioceptive signals from the ankle region. 59 Proprioception can be defined as "the unconscious perception of movement and spatial orientation arising from stimuli within the body," 60 and the unstable support surface forces the central nervous system to down-weight the less reliable ankle muscle proprioception and consequently to up-weight the proprioceptive input from more proximal segments, to provide optimal postural control. 59,61 Nevertheless, a faster performance on an unstable support surface compared with the stable condition was observed.…”
Section: Decreased Cortical Thickness In the Rostral Anterior Cingulamentioning
confidence: 99%
“…59 Proprioception can be defined as "the unconscious perception of movement and spatial orientation arising from stimuli within the body," 60 and the unstable support surface forces the central nervous system to down-weight the less reliable ankle muscle proprioception and consequently to up-weight the proprioceptive input from more proximal segments, to provide optimal postural control. 59,61 Nevertheless, a faster performance on an unstable support surface compared with the stable condition was observed. Because of the nonrandomized order of these conditions, this is possibly due to a learning effect.…”
Section: Decreased Cortical Thickness In the Rostral Anterior Cingulamentioning
confidence: 99%
“…This assumption, however, has been challenged on the basis that wobble board training alone does not actually target ankle proprioception deficits. 17 Kiers et al 17 proposed that training on unstable surface was alone not sufficient to stimulate ankle proprioceptors but did highlight the sensitivity of ankle muscle spindles to vibration stimulus and suggest that muscle spindles are key to ankle proprioception and overall body orientation. These results suggest that clinicians need to consider more effective exercises in ankle rehabilitation and warrant further investigation into the inclusion of vibration stimulus.…”
Section: Introductionmentioning
confidence: 99%